Corruption and Economic Growth in the Balkan Countries - Kadia, Amarda (European Journal of Economics and Business Studies, 2020)
This paper examines the effect of corruption on public debt and economic growth. Empirical analysis verifies the channels that lead to an increase in the public debt, such as a rise in government spending, informal economy, infrastructure spending, always having a budget deficit financed through debt. The underlying hypothesis is that debt has a negative economic consequence in a country and austerity policies have more effect on countries with consolidated finances, while in developing countries such as Albania often bring an even higher growth of public debt. The final objective of this paper is the empirical verification of the idea that in developing countries, such as Albania and Balkan countries, public debt and corruption are inhibitors and deleterious for the economic growth.
Keywords: Corruption and Economic Growth in the Balkan Countries1.